FOLKLORES FROM SOUTH SUMATERA IN ENGLISH: MEDIA TO INTRODUCE INDONESIAN CULTURE TO INTERNATIONAL WORLD - ARMILIA SARI (Sriwijaya University Learning and Education International Conference, 2016)
The objective of this research is to describe culture values which are contained inthree folklores from South Sumatera and its functions as a media to introduceIndonesian culture to international world. This research is a library research. Thedata were gathered by using descriptive method and qualitative approach. As it iswell known, Indonesia has a lot of folklores from 35 provinces as preciousIndonesian wealth, one of them is South Sumatera Province. There are threefolklores from South Sumatera; Legend of Kemaro Island, Legend of Bidar BoatsCompetition, and Semesat and Semesit. Indonesian folklores in English have role tointroduce Indonesian terms, to describe Indonesian culture, and to promoteIndonesian places. By reading the English version of the folklores on this website,people from all over the world can comprehend the stories and its culture values.